Creation of a minimal tiling path of genomic clones for Drosophila: provision of a common resource. (August 2004) - Hollich, Volker; Johnson, Eric; Furlong, Eileen E.; Beckmann, Boris; Carlson, Joseph; Celniker, Susan E.; Hoheisel, Jörg D.
On the basis of shotgun subclone libraries used in the sequencing of the Drosophila melanogaster genome, a minimal tiling path of subclones across much of the genome was determined. About 320, 000 shotgun clones for chromosomes X(12–20), 2R, 2L, 3R, and 4 were available from the Berkeley Drosophila Genome Project. The clone inserts have an average length of 3.4 kb and are amenable to standard PCR amplification. The resulting tiling path covers 86.2% of chromosome X(12–20), 86.2% of chromosomal arm 2R, 79.0% of 2L, 89.6% of 3R, and 80.5% of chromosome 4. In total, the 25, 135 clones represent 76.7 Mb—equivalent to about 67% of the genome —and would be suitable for producing a microarray on a single slide.